The effect of alginate encapsulated plant-based carbohydrate and protein supplementation on recovery and subsequent performance in athletes - Nielsen, L. L. K.; Lambert, M. N. T.; Haubek, D.; Bastani, N. E.; Skålhegg, B. S.; Overgaard, K.; Jensen, J.; Jeppesen, P. B. (Nutrients, 2024)
The main purpose of this study was to investigate the effect of a novel alginate-encapsulated carbohydrate-protein (CHO-PRO ratio 2:1) supplement (ALG) on cycling performance. The ALG, designed to control the release of nutrients, was compared to an isocaloric carbohydrate-only control (CON). Alginate encapsulation of CHOs has the potential to reduce the risk of carious lesions.